Factors Affecting Poverty Level in South Sumatra Indonesia - Jhony Franata; Taufiq Marwa; Muhammad Komri Yusuf (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2017)
The study aims to find out the direct and indirect effect of education, health, government investment and private investment on productivity as well as the poverty level in South Sumatera. The study used secondary data of 2004-2005 published by the Central Bureau of Statistics (BPS), Directorate General of Fiscal Balance (DJPK) and other institutions. It used Path Analysis. The Result of the study show that (1) education, health, and government investment did not directly influence the productivity in South Sumatra, while the private investment directly and positively influenced the productivity in South Sumatra, (2) education, government investment, and private investment did not directly influence the poverty level in South Sumatra, while the health and productivity directly and significantly but negatively influenced the poverty level in South Sumatra, (3) education, health, and government investment indirectly did not influence the poverty level through the productivity in South Sumatra, while the private investment indirectly have significant and negative impact on poverty level through productivity in South Sumatera.